Research Article Titles and Disciplinary Conventions: A Corpus Study of Eight Disciplines - Nagano, Robin L. (Journal of Academic Writing, 2015)
Research articles are clearly influenced by the discipline of the research being reported. Just as disciplinary conventions place constraints on, for example, the moves and language use of abstracts and introductions, they also provide a set of options for title design. This study attempts to identify the title conventions of eight disciplines by focusing on various features that play a part in title design: the use of multiple-unit titles (those with subtitles); the use of noun phrases to form the title; and ’a’ or ’the’ in initial position. The length of titles is investigated, as is the proportion of substantive words. Data is based on a 3,200-title corpus of titles from research articles published in prestigious journals in four disciplines in the hard sciences (botany, fluid engineering, geology, and medicine) and four in the soft sciences (economics, education, history, and sociology). The data is presented in a visual form that compares title features by discipline, to demonstrate title conventions and to help novice writers understand the features and options available.